Community Service Vocational School Management at State I Vocational School Tomohon, Tomohon City - Sumual, Herry (JR Education, 2024)
This research aims to analyze and develop the management of Vocational High Schools (SMK) through the Community Service program at SMK Negeri 1 Tomohon, Tomohon City. The research method used is a qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation. This research is motivated by the important role of vocational schools in preparing skilled workers who are ready to compete in the industrial world. SMK Negeri 1 Tomohon was chosen as the research object because it has unique potential and challenges in implementing effective school management. The research results show that good school management requires collaboration between schools, industry, and society. The aspects analyzed include competency-based curriculum, learning facilities, and the involvement of parents and the community in supporting educational activities. This research found that several areas require improvement, including improving facilities and infrastructure, developing a curriculum that is more relevant to industry needs, and increasing teacher capacity through continuous training. Based on these findings, this research recommends several strategies to improve the management of SMK Negeri 1 Tomohon, namely: (1) increasing collaboration with local industry to provide relevant facilities and training programs, (2) developing community service programs that involve students in projects real, and (3) strengthening the evaluation and monitoring system to ensure sustainable education quality. It is hoped that this research can make a real contribution to the development of vocational school management in Indonesia, especially in the context of community service, as well as encourage the active involvement of all stakeholders in improving the quality of vocational education.